P1240 Outcome of different treatment modalities for gestational trophoblastic neoplasia in women at 40 years old or above: a multicenter retrospective study. (1st November 2019) - Hemida, R; Sauthier, P; Toson, E; Tsip, N; Pradjatmu, H; Eladawy, N; Anfinan, N; Sait, K; van Doorn, HC
Abstract : Introduction/Background: For treatment of GTN patients at old age; there is an ongoing debate about performing upfront hysterectomy to reduce tumor bulk or starting chemotherapy. Methodology: A retrospective analysis of data from 5 referral centers from 5 countries (Egypt, Canada, Ukraine, Saudi Arabia, and Indonesia) during last 5 years. Medical records of 119 women with GTN were retrieved, reviewed and analyzed. Demographic criteria and outcome of different treatment strategies were evaluated. Results: Mean age was 45.46 years, and median hCG was 1390.5 m.IU/ml. Low-risk GTN represented 81.5% of cases while 18.5% were in high-risk group. Most of the patients were in FIGO stage I (76.2%). Metastases were diagnosed in 28 cases (23.5%), lungs were commonest site. The commonest histopathological type was invasive mole (38.1%). Of 80 patients with low risk non metastatic GTN, 32 women were treated with single chemotherapy. Eighteen of them (56.2%) showed complete response while relapse was reported in one case. In 34 cases a hysterectomy was performed. In four; a wait and see policy was adopted while instant chemotherapy followed in 30, mainly single MTX for 1-12 courses. Only one case 1/34 (3%) failed to respond. Of 14 patients with low risk metastatic GTN, 8 women were treated with single chemotherapy while in 6 patients a hysterectomy was performed and MTX was started immediately in all. Complete response occurred only in 7/14 (50%). Two high risk patients died before treatment could start due to presence of distant metastases. Eleven cases had underwent hysterectomy and chemotherapy as first line; 7/11 showed complete response. Four women used EMA/CO combination chemotherapy alone; two of them (50%) had incomplete response and needed 2nd line EMA/EP combination. Conclusion: Upfront hysterectomy for treatment low-risk non-metastatic disease and combination chemotherapy for high-risk disease were associated with better prognosis. Disclosure: Nothing to disclose.